Effect of quercetin and its microstructured forms on cell viability and nuclear DNA degradation in human keratinocytes when modelling oxidative stress - Potapovich, Alla I.; Kostyuk, Tatyana V.; Shutava, Tatsiana G.; Kostyuk, Vladimir A. (Experimental Biology and Biotechnology, 2024)
Experimental data are presented indicating the possibility of using cumoquinone to model oxidative stress and study its consequences in cultured human keratinocytes of the HaCaT line. It has been shown that cell death, DNA damage and the appearance of atypical DNA comets in keratinocytes exposed to cumoquinone are associated not with its genotoxicity, but mainly with the development of oxidative stress. It has been established that quercetin has a cytoprotective effect and reduces the degree of damage to nuclear DNA under conditions of oxidative stress initiated by cumoquinone. This effect increases significantly when microstructured forms of quercetin are used, which may be due to an increase in its cellular availability.
Keywords: HaCaT keratinocytes; p-benzoquinones; quercetin; microstructures; oxidative stress; DNA damage; DNA comets